2020
DOI: 10.1111/ppl.13217
|View full text |Cite
|
Sign up to set email alerts
|

Membrane dynamics during individual and combined abiotic stresses in plants and tools to study the same

Abstract: The plasma membrane (PM) is possibly the most diverse biological membrane of plant cells; it separates and guards the cell against its external environment. It has an extremely complex structure comprising a mosaic of lipids and proteins. The PM lipids are responsible for maintaining fluidity, permeability and integrity of the membrane and also influence the functioning of membrane proteins. However, the PM is the primary target of environmental stress, which affects its composition, conformation and propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 209 publications
(293 reference statements)
1
43
0
1
Order By: Relevance
“…Recent advances evidenced the role of MTs as they are the major shareholder in sugar transportation from leaf (source) to sink (root, stem and seed) via phloem loading and nutrient transportation from roots to upper plant parts through xylem loading [ 2 , 3 ]. Thus, the efficient utilization of MTs not only could help researchers to increase grain yield directly but also expand arable land by improving tolerance mechanisms against various abiotic stresses, i.e., salt, drought, cold, heat and heavy metals (HMs) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances evidenced the role of MTs as they are the major shareholder in sugar transportation from leaf (source) to sink (root, stem and seed) via phloem loading and nutrient transportation from roots to upper plant parts through xylem loading [ 2 , 3 ]. Thus, the efficient utilization of MTs not only could help researchers to increase grain yield directly but also expand arable land by improving tolerance mechanisms against various abiotic stresses, i.e., salt, drought, cold, heat and heavy metals (HMs) [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, some exclusively responded during individual and combined stress, while few showed similar function during individual and combined stress, such as protein kinases, phosphatases, LEA, dehydrins, osmotins, and HSPs [ 19 ]. Osmotic (drought and salinity) stress sensory proteins are mostly localized in the plasma membrane and demonstrate similar response individually but differ during combined stress [ 40 , 198 ]. Similar reports were observed during proteomics and western blot analysis in response to combined drought and heat stresses as glycolate oxidases, catalases and dehydrins were up-regulated during drought, while thioredoxin peroxidase is up-regulated during heat stress.…”
Section: Impact Of Individual Combined and Sequential Stresses On Plantsmentioning
confidence: 99%
“…Here, we will discuss the role of proteins in membrane remodeling. A large number of studies have shown that the contents of lipids, phospholipids, glucolipids, and sterols in the membrane are significantly changed under abiotic stresses such as HMS and high salinity [29,30]. This means that in response to abiotic stresses, plants reshape their membrane lipid composition and use this process to recruit many membrane proteins to resist HMS.…”
Section: Role Cell Membrane Proteins In Hms Tolerance In Plants 21 the Reorganization Of Endomembranesmentioning
confidence: 99%